The Surveillance of Emergent Threats to Maternal and Newborn Health in Indonesia: A Scoping Review - Johnston, Caroline; Nashihah, Prenati; Purnami, Cahya Tri; Martini, Martini (Journal of Public Health for Tropical and Coastal Region, 2024)
Introduction: Indonesian Ministry of Health has emphasized the need to effectively identify and respond to emergent threats (ET) to maternal and newborn health (MNH), including non-communicable and infectious diseases. Improved ET screening, surveillance, and data management will reduce poor MNH outcomes including mortality, stillbirth, prematurity, and low birthweight. This scoping review examines practices of surveillance of ET to MNH, both globally and in Indonesia.Methods: Fifty-nine articles published between 2011 to 2024, sourced from PubMed and Google Scholar were reviewed. Thirteen articles were included in the final scoping review. The key search terms included “emergent threat surveillance”, “maternal and newborn health”, “MNH surveillance”, “PWS-KIA”, and “SatuSehat”.Results: The review identified numerous gaps in MNH surveillance, including a need for comprehensive data sharing between health facility, district, provincial, and national levels. Additionally, midwives reported that the current MNH monitoring system, PWS-KIA (Local Area Monitoring Health of Mother and Child), is time-consuming and confusing, leading to poor data reporting. Finally, due to limited training of health workers, there is a lack of data analyzation at each level, leading to poor response.Conclusion: An integrated, standardized, and user-friendly system is needed to detect and mitigate emergent threat to maternal and neonatal health. Data analysis and response to adequately identify and reduce emergent threat at each level is critical.  Routine training is needed to improve health provider knowledge on data interpretation and use.